Limitation of exposure to ionizing radiation : recommendations of the National Council on Radiation Protection and Measurements. (The Council, 1993)
"This is the latest in the long series of reports on basic radiation protection criteria that began in 1934. It supersedes the predecessor in the series, NCRP Report No. 91, which was published in 1987. The current Report takes advantage of new information, evaluations and thinking that have developed since 1987, particularly the risk estimate formulations set out in NCRP Report No. 115. While the recommendations set out in this Report do not constitute a radical revision of the basic criteria, they do represent a refinement of the system enunciated in Report No. 91. Important changes include the utilization of revised tissue/organ weighting factors and the introduction of radiation weighting factors. Also noteworthy is the introduction of an allowable reference level of intake. Noteworthy too is the recommendation of an age-based lifetime limit for control of occupational exposures and a major simplification of limits aimed at controlling the exposure of the embryo and fetus."--Knovel's description
"Issued March 31, 1993."
Keywords: Ionizing radiation -- Safety measures.; Ionizing radiation.; elektronické knihy; electronic books